Functional outcomes of intra-articular calcaneal fractured patients who had been treated operatively and non-operatively in Queen Elizabeth Hospital, Kota Kinabalu, Sabah from June 2009 to May 2013 - Kien Loong, Chan (2015)
INTRODUCTION: Calcaneal fractures are caused by high energy trauma and mostly are intra-articular fractures. Non-displaced intra-articular calcaneal fracture (IACF) can be treated non-operatively. Displaced intra-articular need to be reduced and fixed anatomically to facilitate early ankle rehabilitation and minimize functional impairment. This study intends to find out the functional outcome of the IACF patients who were underwent operative treatment compared with patients who treated non-operatively. METHODS: This study was a cross-sectional, single-intervention and retrospectively assessed the selected 62 patients with IACF, who had fulfilled inclusion and exclusion criterias. All patients recruited in this study were from June 2009 to May 2013 and sampled into two groups; the operative treatment and non-operative treatment groups. The patient’s bilateral foot lateral view plain radiographs will be taken for comparison of the Bohler’s angle. Both groups of patients were assessed by the SF-36v2 health survey questionnaire and their ability to perform ADLs or RTW was being assessed as well. RESULTS: achieved no significantly better result in the PCS and MCS scores if compared with the non-operative treatment group. The Bohler’s angle was found to have direct correlation with the functional outcome. In addition, the operative treatment group of displaced IACF patients not achieved significant earlier RTW or performs ADLs when compared with the non-operative treatment group. CONCLUSIONS: If compared with the undisplaced IACF patients which had treated non-operatively, the operative anatomical restoration and fixation of the displaced IACF is essential to provide as similar as, but not significant better functional outcome as well as early RTW and performs ADLs.